An Efficient Ultrasonic-Assisted Synthesis of Enol Carbamates via Oxidative Coupling of Formamides with 1,3-Dicarbonyl Compounds - Akbari, Jafar; Meyestani, Alireza A. (Letters in Organic Chemistry, 2020)
Sonochemical oxidative-coupling of formamides with 1,3-dicarbonyl compounds in the corresponding carbamates by CuO nanoparticles as a catalyst and tert-butyl hydroperoxide (TBHP) as an oxidant has been reported. Various derivatives of enol carbamates were synthesized with good to high yields under the optimized reaction conditions. Compared with conventional methods, the main advantage of this method is mild conditions.
Keywords: carbamates